Aeolian Empires: The Influence of Winds and Currents on European Maritime Expansion in the Days of Sail. (1st May 2017) - Bankoff, Greg
Abstract : Historiography has paid insufficient attention to the influence of winds and currents. The rise of Western European states to global dominance and world empires from the sixteenth century is usually characterised as maritime but should more fittingly be described as Aeolian or 'wind-driven'. This article examines the role winds and currents played in influencing the outline, structure and nature of Western European seaborne empires. It incorporates the patterns of winds and currents in each ocean, and the endeavours and ventures of each major European maritime power into a single global portrait that reveals the extent of the historical influence such factors exerted in the age of sail.